Cyanuryl peptide nucleic acid: synthesis and DNA complexation properties - Vysabhattar, Raman; Ganesh, Krishna N. (Tetrahedron Letters, 2008)
The synthesis of cyanuryl PNA monomer (CyaPNA) 6 was achieved by direct N-monoalkylation of cyanuric acid with N-(2-Boc-aminoethyl)-N'-(bromoacetyl)glycyl ethyl ester 4. Compound 6 was incorporated as a T-mimic into PNA oligomers and biophysical studies on their triplexes/duplex complexes with complementary DNA oligomers indicated unusual stabilization of PNA:DNA hybrids when the cyanuryl unit was located in the middle of the PNA oligomer. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: cyanuryl PNA; PNA

In situ, on-resin synthesis of 8-Br/NH2 adeninyl peptide nucleic acid (PNA) oligomers and complementation studies with DNA - Vysabhattar, Raman; Ganesh, Krishna N. (Tetrahedron Letters, 2010)
A new, novel and efficient in situ synthesis of 8-aminoadeninyl PNA oligomers from corresponding 8-bromoadeninyl PNA oligomers is reported. The study of hybridisation properties of (8-Br/8-NH2) PNA oligomers with cDNA reveals substitution-site dependent stabilization of derived triplexes and duplexes. (C) 2010 Elsevier Ltd. All rights reserved.